2022
DOI: 10.1002/pmrj.12745
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐disciplinary collaborative consensus guidance statement on the assessment and treatment of cognitive symptoms in patients with post‐acute sequelae of SARS‐CoV‐2 infection (PASC)

Abstract: Note: This table is included in the Appendix to provide additional information for clinicians who are treating patients for PASC-related cognitive symptoms. This is not intended to be a comprehensive list, but rather to provide clinical examples as they relate to health equity, health disparities, and social determinants of health. The literature demonstrates that all marginalized groups face socioeconomic barriers and access to care barriers, though these may or may not be barriers for a specific individual p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
48
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 38 publications
(66 citation statements)
references
References 62 publications
(37 reference statements)
0
48
0
Order By: Relevance
“…Post-exertional malaise may be described as “crashing” after several good days, or several days of worsening symptoms after stressors or triggers. Cognitive difficulties or “brain fog” can include impaired attention, concentration, reduced ability to multi-task, difficulty with short-term memory and word-finding difficulties 72 . Some patients may describe increased irritability or emotionally vulnerability.…”
Section: Considered Approach To the Evaluation Of Patients With Long ...mentioning
confidence: 99%
See 4 more Smart Citations
“…Post-exertional malaise may be described as “crashing” after several good days, or several days of worsening symptoms after stressors or triggers. Cognitive difficulties or “brain fog” can include impaired attention, concentration, reduced ability to multi-task, difficulty with short-term memory and word-finding difficulties 72 . Some patients may describe increased irritability or emotionally vulnerability.…”
Section: Considered Approach To the Evaluation Of Patients With Long ...mentioning
confidence: 99%
“…Although there are few studies of treatment in Long COVID that have shown efficacy or effectiveness, consensus guidance on best approaches to treat these patients based on the lived experience of patient and clinicians are emerging 71 , 72 , 73 , 80 . The overall approach to treatment of Long COVID is to focus on managing symptoms, improving function, and working with the patient to settle on reasonable treatments targets that have the potential to improve their quality of life.…”
Section: Considered Approach To the Evaluation Of Patients With Long ...mentioning
confidence: 99%
See 3 more Smart Citations